Frequent overexpression of epidermal growth factor receptor (EGFR) in mammary high grade ductal carcinomas with myoepithelial differentiation. Issue 12 (25th November 2005) - Shien, T; Tashiro, T; Omatsu, M; Masuda, T; Furuta, K; Sato, N; Akashi-Tanaka, S; Uehara, M; Iwamoto, E; Kinoshita, T; Fukutomi, T; Tsuda, H; et al.
Abstract : Aims: To evaluate the expression of common biological markers and the epidermal growth factor receptor (EGFR) in mammary high grade ductal carcinomas with myoepithelial differentiation (DCMDs). Materials/methods: Thirty DCMDs were clinicopathologically and immunohistochemically analysed and compared with 36 control cases of high grade conventional invasive ductal carcinoma (IDC). Results: EGFR, HER2/neu, oestrogen receptor, progesterone receptor, and p53 expression was seen in 21, one, three, four, and 20 of the 30 DCMDs, compared with eight, nine, 18, 17, and five of the 36 conventional IDCs (p < 0.05), respectively. In 16 of the 30 DCMDs, metastases were found in the brain, lung, bone, and liver, within a maximum of 47 months (mean, 13.9) after initial surgery, whereas only four of the 36 conventional IDCs metastasised to the lung and bone within a maximum of 27 months (mean, 18.0) after initial surgery (p = 0.0001). There was a significant difference in disease free survival between DCMD and conventional IDC (p = 0.001). EGFR was frequently overexpressed in DCMD compared with conventional IDC, whereas the expression of HER2/neu and hormone receptors was lower in DCMD. Fluorescent in situ hybridisation revealed that the mean EGFR to chromosome 7 centromere (CEP7) ratio of the 24 DCMD cases available for evaluation was 1.03, and EGFR gene amplification was not detected in the 21 DCMD cases with EGFR overexpression. Conclusion: Immunohistochemistry for myoepithelial markers and EGFR is useful for the accurate diagnosis and molecular target treatment of high grade DCMD.